Historical Analogy: Japan’s Road Toward War and Japan’s Postwar Road - Xiaoran, Wang (Cultural and religious studies, 2016)
In 1931, Japan launched the Sept. 18th attack against China. Ever since, there have been many different views over the origin of Japan’s road toward war, which mostly concern with Japan’s land policy. This paper holds that Japan’s land policy was an evolving one and it transformed along the change of its supporters and implementers during different stages. It is mostly a contention about the different strategies on Manchuria and Mongol; the northward or the southward advance faction; the orientations of the radical military occupation or the moderate economic occupation. Interestingly, the development of Japan’s postwar policy toward China, especially in the recent years, resembles the evolvement of Japan’s land policy in the 19th century. They both show tendency from the economic effort to the military activity.